Diagnosis of Paroxysmal Nocturnal Hemoglobinuria in a pregnant woman with thrombocytopenia for 04 years: Case Report (Research, Society and Development, 2022)
Paroxysmal Nocturnal Hemoglobinuria (PNH) is a rare clonal somatic exchange disorder manifested by a stem cell disorder with clinical features of hemolytic anemia, bone marrow deficiency and thromboembolism. The disease affects both sexes, with a higher prevalence after 40 years old and an incidence of 1 event in a million people, an affection that is rare and little reported in the literature, a fact observed even more in pregnant women. The aim of this study is to report the case of a young, pregnant patient who had been suffering from idiopathic thrombocytopenia for 4 years and was diagnosed as Paroxysmal Nocturnal Hemoglobinuria (PNH) during pregnancy. The information was obtained through medical records review, complementary exam records, and literature review. The young pregnant woman presented with mild anemia, persistent thrombocytopenia and recurrent urinary infection throughout the gestational period, and despite being diagnosed with thrombocytopenia in the third trimester, still had a favorable gestational outcome.